Renal Safety of Long-Term Antihypertensive Therapy: A Systematic Review - Thendi Abdul Arief; Yohanna Lawanda da Costa; Niky Budiarti; Luthfiah Pertiwi; Agung Endro Nugroho; Zullies Ikawati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2026)
Background: Managing hypertension, a major risk factor for chronic kidney disease (CKD), requires long-term antihypertensive medication. However, clinical judgment and medication adherence are impacted by ongoing worries about its renal safety.Objectives: This study aimed to systematically evaluate and compare the renal safety profiles of antihypertensive drug classes during long-term use (>6 months) in hypertensive patients.Methods: Following the PRISMA 2020 principles, a systematic review was carried out. A thorough search of PubMed and ScienceDirect from 2015 to April 2025 was conducted ("ACEi OR ARB OR CCB OR Beta Blocker OR Diuretic AND Hypertension AND long-term use AND Renal Function"). A narrative synthesis was carried out in compliance with the Synthesis Without Meta-Analysis (SWiM) guideline due to clinical and methodological heterogeneity.Results: A total of 7214 studies were retrieved and reviewed. Only five papers were chosen after additional analysis. In comparison to CCBs in advanced chronic kidney disease (CKD), diuretics in combination with renin-angiotensin system inhibitors (RASi) were linked to a decreased incidence of significant adverse renal events (weighted HR 0.87, 95% CI 0.77-0.97). Despite a higher frequency of reversible eGFR drop and hyperkalemia, continuous ACEi/ARB treatment before dialysis initiation significantly decreased post-dialysis mortality (aHR 0.87, 95% CI 0.83-0.92). Compared to amlodipine, ACEi alone reduced eGFR and raised serum levels of potassium and creatinine for at least a year. In patients with resistant hypertension and baseline eGFR ≥30 mL/min/1.73 m², spironolactone successfully reduced blood pressure; however, initial elevations in serum creatinine and potassium needed to be monitored. Since blood pressure was well controlled, there was no discernible difference between ARBs and CCBs regarding the risk for end-stage kidney disease (HR 0.28; CI 0.14-0.58).Conclusion: Combining RASi with a diuretic provides superior renal protection for CKD patients compared to CCB. Post-dialysis mortality is also decreased by long-term ACEi/ARB usage. Under careful supervision, spirolactone is both safe and effective. Thus, regular use of ACEi/ARB and diuretic-RASi combination therapy is a safe and effective long-term method for maintaining renal function in hypertension.